Online monitoring of transformers using gas sensor fabricated by nanotechnology. (9th August 2012) - Chatterjee, Anjali; Sarkar, Rajat; Roy, Nirmal K.; Kumbhakar, P.
SUMMARY: Power transformers are key elements in a power system. Hence, their maintenance is essential for uninterrupted power supply. In line with this demand, a portable, online diagnostic analyzer is designed which is able to collect temperature data and quantify the concentration of some of the dissolved gases in transformer oil with the help of a non‐invasive sensor fabricated by nanotechnology methodology. After conditioning the signals appropriately, the data are transmitted to the substation for storage. The computer also has the ability to remotely access the data for analysis and assess the health of the transformers. From the data of three gases, different faults, if they are occurring inside the transformer, can be predicted. The fault diagnosis is done by dissolved gas analysis, which is one of the proven methods widely used during the last two decades. Copyright © 2012 John Wiley & Sons, Ltd.